Maxillary Constriction with Skeletal Class II Malocclusion - A Comprehensive Treatment Approach. - Yezdani Arif; Fathima Jabeen (Journal of Dentistry And Oral Implants, 2016)
This case report reiterates the fact that a bilateral posterior crossbite with severe skeletal class II malocclusion in the growth period could be effectively treated by a comprehensive approach with a rapid palatal expansion appliance followed by fixed appliance therapy. A 14-year-old boy presented with a severe skeletal Class II malocclusion with an orthognathic maxilla, retrognathic mandible and a high mandibular plane angle with an Angles’ Class II division 1 subdivision malocclusion with maxillary constriction, increased overjet, deep bite and severe crowding of maxillary and mandibular incisors. A banded rapid palatal expansion appliance was initially given to correct the bilateral posterior cross bite and subsequently maxillary and mandibular first premolars were extracted and Roths’ Pre adjusted edgewise appliance therapy (0.022 x 0.28-inch slot) was strapped up to correct the severe tooth size-arch length discrepancy. The patient’s soft tissue profile and dentofacial esthetics improved dramatically with increased self-confidence and enthused self-esteem.
Keywords: bilateral maxillary posterior cross-bite